2022
DOI: 10.1002/ijc.34125
|View full text |Cite
|
Sign up to set email alerts
|

Survival after neoadjuvant/induction combination immunotherapy vs combination platinum‐based chemotherapy for locally advanced (Stage III) urothelial cancer

Abstract: Despite treatment with cisplatin-based chemotherapy and surgical resection, clinical outcomes of patients with locally advanced urothelial carcinoma (UC) remain poor.We compared neoadjuvant/induction platinum-based combination chemotherapy (NAIC) with combination immune checkpoint inhibition (cICI). We identified 602 patients who attended our outpatient bladder cancer clinic in 2018 to 2019.Patients were included if they received NAIC or cICI for cT3-4aN0M0 or cT1-4aN1-3M0 UC. NAIC consisted of cisplatin-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Some have rather short follow-up, while others have been very recently updated. [33][34][35] Trial comparison is obviously difficult in view of different patient populations included (clinical T stage and N stage, cisplatin eligible v ineligible, and geographic region) but overall pCR and pathologic response <ypT2 appear similar in all studies, including ours, with rates of 30%-40% and 55%-65%, respectively. An interesting comparison can be done with the results from the perioperative VESPER trial that compared the cisplatin-based and immunotherapyfree regimens of GC and ddMVAC demonstrating a benefit for the use of ddMVAC with a pCR rate of 42% and an EFS at 2 years of approximately 77%.…”
Section: Discussionmentioning
confidence: 76%
“…Some have rather short follow-up, while others have been very recently updated. [33][34][35] Trial comparison is obviously difficult in view of different patient populations included (clinical T stage and N stage, cisplatin eligible v ineligible, and geographic region) but overall pCR and pathologic response <ypT2 appear similar in all studies, including ours, with rates of 30%-40% and 55%-65%, respectively. An interesting comparison can be done with the results from the perioperative VESPER trial that compared the cisplatin-based and immunotherapyfree regimens of GC and ddMVAC demonstrating a benefit for the use of ddMVAC with a pCR rate of 42% and an EFS at 2 years of approximately 77%.…”
Section: Discussionmentioning
confidence: 76%
“…Still, these results offer ground for comparative studies with standard of care chemotherapy. A retrospective cohort study comparing a contemporary platinum-based NAC cohort to the NABUCCO cohort suggested a benefit in OS in favour of combination ICI [31]. As of writing, there are two ongoing phase II trials studying perioperative anti-CTLA-4/PD-(L)1 combinations.…”
Section: Combined Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…We thank Dr Takahashi for the comments on our study. 1 We would like to take the opportunity to address these and to clarify our position on the role of preoperative platinum-based chemotherapy (NAIC) or combination immune checkpoint inhibition (cICI) and cystectomy in patients with locally advanced urothelial carcinoma (cT3-4aN0M0 or cTanyN+M0 UC).…”
Section: Dear Editormentioning
confidence: 99%
“…
Dear editor,We thank Dr Takahashi for the comments on our study. 1 We would like to take the opportunity to address these and to clarify our position on the role of preoperative platinum-based chemotherapy (NAIC) or combination immune checkpoint inhibition (cICI) and cystectomy in patients with locally advanced urothelial carcinoma (cT3-4aN0M0 or cTanyN+M0 UC).The commenter argues that cystectomy is not indicated for patients with cTanyN+M0 UC-that is, for patients in the induction setting. However, our treatment of patients in the induction setting conforms to the clinical guidelines of the National Comprehensive Cancer Network, which recommend cystectomy in patients with response to systemic treatment.
…”
mentioning
confidence: 99%
See 1 more Smart Citation